2022
DOI: 10.3389/fpsyg.2022.977466
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Empirical analysis of the impact of China–Japan–South Korea transportation infrastructure investment on environmental degradation and the validity of the environmental Kuznets curve hypothesis

Abstract: Building sustainable and affordable transport systems is a key issue for social development and sustainable urban expansion. The study used dynamic ordinary least squares (DOLS) and fully modified ordinary least squares (FMOLS) to examine the impact of transport infrastructure investment on environmental degradation in China, Japan, and South Korea over the period 1995–2020 and the validity of the EKC hypothesis. The results show that GDP has a significant positive effect, and GDP2 and GDP3 have significant ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 127 publications
0
3
0
Order By: Relevance
“…The results of the analysis did not confirm the validity of the EKC assumptions for selected economies. Lu et al (2022) applied dynamic ordinary least squares (DOLS) and fully modified ordinary least squares (FMOLS) to examine the validity of EKC China, Japan, and South Korea over the period 1995-2020. The results show that GDP significantly promotes environmental degradation and GDP2 significantly reduces environmental degradation, thus validating the inverted U-shaped EKC hypothesis in selected Asian countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of the analysis did not confirm the validity of the EKC assumptions for selected economies. Lu et al (2022) applied dynamic ordinary least squares (DOLS) and fully modified ordinary least squares (FMOLS) to examine the validity of EKC China, Japan, and South Korea over the period 1995-2020. The results show that GDP significantly promotes environmental degradation and GDP2 significantly reduces environmental degradation, thus validating the inverted U-shaped EKC hypothesis in selected Asian countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many prior studies such as [ 16 , 31 , 38 , 42 45 ] have shown that the vital driver of environmental damage is urbanization. However, studies such as [ 46 67 ] have shown that environmental damage can be controlled through the use of renewable energy sources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By replacing diesel locomotives with electric trains powered by renewable or cleaner energy sources, it's possible to significantly reduce greenhouse gas emissions. This shift not only contributes to climate change mitigation but also improves air quality and reduces noise pollution in urban areas near railway lines [48].…”
Section: Carbon Emission Characteristics Of Railwaysmentioning
confidence: 99%